(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
In the organizational literature, we can find two different propositions about therelation between vertical integration and quality. The first one highlights the specialization in the core business. The second emphasize the integrated forms coordinationand the easy communication to achieve superior performance. In this article we carry out a revision of theoretical literature and an empiricalstudy in the Galician construction industry, and we contrast that the specializationfavours getting certifications ISO, and the certifications favour the integration.